SYSTEMATIC REVIEW OF THE INFLUENCE OF BRAND IMAGE, PRODUCT QUALITY, PRICE, AND PROMOTION ON PURCHASE INTENTION THROUGH CUSTOMER SATISFACTION - Vidya Damayanti; Budi Eko Soetjipto; Ludi Wisnu Wardhana (RADJA PUBLIKA, 2025)
Consumer behavior in shaping purchase intention has become a primary focus in modern marketing literature. This study employs the Systematic Literature Review (SLR) method to analyze 82 articles published over the past five years, examining the influence of brand image, product quality, price, and promotion on purchase intention, with customer satisfaction as the main mediating variable. The findings indicate that all four variables significantly affect purchase intention, both directly and indirectly through customer satisfaction. Brand image and customer satisfaction emerge as central affective elements, while product quality and price are increasingly perceived through symbolic and psychological interpretations. Promotion has transformed into an engagement-oriented channel focused on value creation. This study reinforces classical theories while proposing an integrative multi-path interaction model, contributing theoretically to the contemporary framework of consumer behavior and offering practical implications for marketing strategies centered on engagement, value creation, and customer satisfaction.